"An Opportunity to Grow Our Collective Consciousness": Navigating Racial Tension in a Gentrifying Elementary School. (March 2023) - Ayscue, Jennifer B.; Beam, Lindsey; Mordechay, Kfir
As gentrification changes the racial and socioeconomic composition of many neighborhoods across the United States, the enrollment of local schools in gentrifying communities may also change. While gentrification may provide opportunities for creating more diverse schools, challenges often accompany such changes. In this case, Principal Miller navigates tensions associated with supporting the school's intentionally diverse and antiracist mission on a daily basis and in response to a noteworthy event—the January 6, 2021 insurrection at the United States Capitol. He grapples with how to build community and address racism among the adult members of the school community, including parents and teachers.